Chronic kidney disease and diabetes in the National Health Service: a cross‐sectional survey of the UK National Diabetes Audit. Issue 4 (1st October 2013) - Hill, C. J.; Cardwell, C. R.; Patterson, C. C.; Maxwell, A. P.; Magee, G. M.; Young, R. J.; Matthews, B.; O'Donoghue, D. J.; Fogarty, D. G.
Abstract Aims We investigated the prevalence of chronic kidney disease and attainment of therapeutic targets for HbA1c and blood pressure in a large UK‐based diabetes population. Methods The UK National Diabetes Audit provided data from 1 January 2007 to 31 March 2008. Inclusion criteria were a documented urinary albumin:creatinine ratio and serum creatinine. Patients were stratified according to chronic kidney disease stage and albuminuria status. Chronic kidney disease was defined as an estimated glomerular filtration rate < 60 ml min−1 1.73 m−2, albuminuria or both. The proportions of patients achieving nationally defined glycaemic and systolic blood pressure targets were determined. Results The cohort comprised 1 423 669 patients, of whom 868 616 (61%) met inclusion criteria. Of the patients analysed, 92.2% had Type 2 diabetes. A higher proportion of people with Type 2 diabetes (42.3%) had renal dysfunction compared with those with Type 1 diabetes (32.4%). Achievement of systolic blood pressure and HbA1c targets was poor. Among people with Type 1 diabetes, 67.8% failed to achieve an HbA1c < 58 mmol/mol (7.5%). Of all people with diabetes, 37.8% failed to achieve a systolic blood pressure < 140 mmHg. Blood pressure control was poor in advanced chronic kidney disease. For example, mean (standard deviation) systolic blood pressure rose from 128.6 (15.4) mmHg among people with Type 1 diabetes and normal renal function to 141.0 (23.6) mmHg in those with chronic kidney disease stage 5 and macroalbuminuria. Conclusions The high prevalence of chronic kidney disease and poor attainment of treatment targets highlights a large subset of the diabetes population at increased risk of cardiovascular mortality or progressive kidney disease.